COVID-19 PANDEMIC AND VIRTUAL CLINIC FOR DIABETES CARE: A SINGLE-CENTRE EXPERIENCE - S, Sazuan; IA, Ida; Y, Yusniza (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The COVID-19 pandemic and increasing prevalence of diabetes combined with a growing shortage of new healthcare professionals presented an opportunity to digitalize diabetes care and rapidly implement virtual diabetes clinics with the aim of optimizing diabetes management and well-being while keeping patients safe, improve efficiency and reduce disease burden. We present our experience in managing our own virtual diabetes clinic in Hospital Sungai Buloh during the COVID-19 pandemic. METHODOLOGY We conducted a quantitative real time data collection between July 2020 until October 2022 from patients who attended the virtual diabetes educator clinic in Hospital Sungai Buloh. All patients received usual diabetes care along with the virtual clinic follow-up. The primary objective was to evaluate the effectiveness of a virtual diabetes clinic on HbA1c reduction, frequency of SMBG and patient satisfaction. RESULT Twenty nine (29) patients were seen in 2020, while 155 patients and 202 patients were seen in 2021 and 2022 respectively, demonstrating an increase of about 47 patients in a year. HbA1c levels before the virtual clinics ranged 8-12% and was reduced to a lower range of <6.5% to 10% after the virtual clinic sessions. Twenty eight (28) patients were able to achieve HbA1cof <6.5% within 8 months. All patients were able to comply with a self-blood glucose monitoring regimen (pre-meals and fasting) and were monitored every three weeks. We also saw an increase in the number of referrals from other departments such as obstetrics, paediatric and surgical based units, from 2 to 29 patients. CONCLUSION Virtual consultations, especially following the COVID-19 pandemic have proven to be crucial in maintaining a line of communication with people with diabetes, encouraging self management remotely and reducing treatment burden. The virtual diabetes clinics in Hospital Sungai Buloh ensured better glucose control and implementation of good lifestyle modification despite COVID-19 restrictions.